Dynamics of canopy structure and soil surface cover in a semiarid grassland - Goff, Bruce Franklin. (The University of Arizona., 1985)
Characteristics of canopy structure and soil surface cover are necessary parameters in hydrologic models of arid and semiarid watersheds. In order to quantify these characteristics, two study sites were established on an experimental watershed in southeastern Arizona, and periodic measurements were made during the 1983 summer/fall growing season. During this period, maximum mean foliage height ranged 10-12 cm on the two study sites, while maximum mean foliage mass and foliage cover ranged 67-105 g/m2 and 30-51%, respectively. Mean live leaf area index (LAI), calculated from foliage mass data, peaked at 0.6-0.7. Mean soil surface cover averaged 34-57%. In general, little change was observed in the measured characteristics on either site during the season. Although the two sites differed considerably in foliage and surface covers, they were similar in foliage mass and LAI.